“The Fish Dies by Its Mouth”:: How Consumers Understand Food Risks Related to Pesticides and GMOs - Galindo, Flavia; Portilho, Fatima (Sustainability in Debate, 2015)
Brazil is touted as the world’s largest user of pesticides - although is not the world’s largest agricultural producer. This data provided the basis for our research about Brazilian consumers’ perceptions about food risks related to pesticides and GMOs, from the logic of food consumption. Using Focus Group with 86 respondents, this research showed that these risks are perceived by Brazilian consumers as intangible or invisible, although they may result in chemical contamination and unintended consequences for possible harmful substances found in food. Besides, the results showed that there is few information and low general awareness of these health risks by Brazilian families. We conclude that, despite the abundance of available information, the knowledge of Brazilian consumers about food risks still wanders between ignorance and unawareness.